Early EEG Findings and Hi-Encephalopathy Outcomes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The value of the EEG as a predictor of outcome in term infants with hypoxic-ischemic encephalopathy (HIE) was determined in a study at Cork University Maternity Hospital and St Vincent's University Hospital, Dublin, Ireland.